Complex DNA structures trigger copy number variation across the Plasmodium falciparum genome. Issue 4 (21st December 2018) - Huckaby, Adam C; Granum, Claire S; Carey, Maureen A; Szlachta, Karol; Al-Barghouthi, Basel; Wang, Yuh-Hwa; Guler, Jennifer L
Abstract: Antimalarial resistance is a major obstacle in the eradication of the human malaria parasite, Plasmodium falciparum . Genome amplifications, a type of DNA copy number variation (CNV), facilitate overexpression of drug targets and contribute to parasite survival. Long monomeric A/T tracks are found at the breakpoints of many Plasmodium resistance-conferring CNVs. We hypothesize that other proximal sequence features, such as DNA hairpins, act with A/T tracks to trigger CNV formation. By adapting a sequence analysis pipeline to investigate previously reported CNVs, we identified breakpoints in 35 parasite clones with near single base-pair resolution. Using parental genome sequence, we predicted the formation of stable hairpins within close proximity to all future breakpoint locations. Especially stable hairpins were predicted to form near five shared breakpoints, establishing that the initiating event could have occurred at these sites. Further in-depth analyses defined characteristics of these 'trigger sites' across the genome and detected signatures of error-prone repair pathways at the breakpoints. We propose that these two genomic signals form the initial lesion (hairpins) and facilitate microhomology-mediated repair (A/T tracks) that lead to CNV formation across this highly repetitive genome. Targeting these repair pathways in P. falciparum may be used to block adaptation to antimalarial drugs.